The Causes of Preference Reversal - Tversky, Amos; Slovic, Paul; Kahneman, Daniel (American Economic Review, 1990)
Observed preference reversal (PR) cannot be adequately explained by violations of independence, the reduction axiom, or transitivity. The primary cause of PR is the failure of procedure invariance, especially the overpricing of low-probability high-payoff bets. This result violates regret theory and generalized (nonindependent) utility models. PR and a new reversal involving time preferences are explained by scale compatibility, which implies that payoffs are weighted more heavily in pricing than in choice.